2021
DOI: 10.1128/iai.00788-20
|View full text |Cite
|
Sign up to set email alerts
|

Taurine-Mediated IDOL Contributes to Resolution of Streptococcus uberis Infection

Abstract: Metabolic alterations occur in pathogen infections, but the role of lipid metabolism in the progression of bacterial mastitis is unclear. Crosstalk between lipid droplets (LDs) and invading bacteria occurs and targeting of de novo lipogenesis inhibits pathogen reproduction. Herein, we investigate the role(s) of lipid metabolism in mammary cells during Streptococcus uberis (S. uberis) infection. Our results indicate that S. uberis induces the synthesis of fatty acids and production of LDs. Importantly, taurine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…Inflammation was involved in the development of mastitis (17). The invading bacteria could activate the innate immune system and lead to the production of inflammatory and oxidative mediators (18). These increased inflammatory mediators such as TNF-a, IL-1ß and IL-6 contributed to the pathogenesis of mastitis (19).…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation was involved in the development of mastitis (17). The invading bacteria could activate the innate immune system and lead to the production of inflammatory and oxidative mediators (18). These increased inflammatory mediators such as TNF-a, IL-1ß and IL-6 contributed to the pathogenesis of mastitis (19).…”
Section: Discussionmentioning
confidence: 99%
“…LD formation occurs during the infection of macrophages with numerous intracellular pathogens, including S. uberis. A previous study in our laboratory found that S. uberis specifically induces LD formation as a pathogenic strategy to create a depot of host lipids for use as a carbon source to fuel intracellular bacterial growth in mammary epithelial cells [18]. Herein, we show that LD formation is not a bacterially driven process during S. uberis infection but rather occurs as a result of immune activation of macrophages as part of a host defence mechanism.…”
Section: Discussionmentioning
confidence: 56%
“…The level of LDs is closely related to lipid metabolism. Previous results in our laboratory have shown that S. uberis infection changes fatty acid synthesis pathways in mammary epithelial cells [18] and in mice [28]. We sought to confirm whether the bacteria have a similar effect on macrophages.…”
Section: S Uberis Increases Fatty Acid Synthesis In Macrophagesmentioning
confidence: 88%
See 2 more Smart Citations